Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00259-009-1346-z
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and radiation dosimetry of [11C]choline: a comparison between rat and human data

Abstract: The absorbed radiation doses after administration of 460 MBq of [(11)C]choline were low. Except for the pancreas, biodistribution in the rat was in accordance with that in humans, but rat data may underestimate the effective dose, suggesting that clinical measurements are needed for a more detailed estimation. The observed effective doses suggest the feasibility of [(11)C]choline PET for human studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Radiation dosimetry estimates for 11 C-sarcosine resulted in an effective dose of 0.0045 mSv/MBq, which is similar to that of 11 C-choline and compares favorably to 18 F-FDG and many other 11 C-labeled radiopharmaceuticals (31). Our absorbed radiation dose measurements confirmed that 11 C-sarcosine can be safely administered to humans.…”
Section: Discussionsupporting
confidence: 67%
“…Radiation dosimetry estimates for 11 C-sarcosine resulted in an effective dose of 0.0045 mSv/MBq, which is similar to that of 11 C-choline and compares favorably to 18 F-FDG and many other 11 C-labeled radiopharmaceuticals (31). Our absorbed radiation dose measurements confirmed that 11 C-sarcosine can be safely administered to humans.…”
Section: Discussionsupporting
confidence: 67%
“…For example, the mean effective dose of 11 C-MET, 11 C-acetate, 11 C-MeAIB, and 11 C-choline was 5.2E-03, 4.9E-03, 4.0E-03, and 4.4E-03 mSv/MBq respectively. 8,[17][18][19] The whole-body PET imaging revealed a mean effective dose of 4.03E-03 mSv/MBq of 11 C-MCYS, which was comparable to or lower than that of the PET imaging tracers previously mentioned. The data showed that routinely used activities of 370 to 555 MBq (10-15 mCi) of 11 C-MCYS in a single PET imaging would lead to an estimated effective dose of 1.49 to 2.24 mSv, which is within the 1-to 10-mSv range of effective doses that are acceptable for volunteers in biomedical research and is also below the 50-mSv effective dose per year limit established by the National Institutes of Health for research subjects.…”
Section: Discussionmentioning
confidence: 93%
“…16 In comparison to 11 C-choline, the total effective dose derived by 18 F-fluciclovine PET/CT administration to an average patient is mildly higher because 11 C-choline delivers approximately 0.0044 mSv/MBq (approximately 2 mSv). 17 In 1 study presenting preliminary results on 15 patients, the authors proved that 18 F-fluciclovine uptake in PCa lesions, both within and outside the prostate, is significantly and persistently increased, prompting for a wider and more systematic trial. 5 One limitation of the tracer regards its increased uptake in both benign prostatic hyperplasia and prostatitis, reducing significantly its specificity for the detection of primary PCa and residual intraprostatic cancer after radiotherapy.…”
Section: Discussionmentioning
confidence: 95%